2020
DOI: 10.47717/turkjsurg.2020.4765
|View full text |Cite
|
Sign up to set email alerts
|

Transoral endoscopic thyroidectomy vestibular approach (TOETVA): Our outcomes from Turkey

Abstract: Objective: The Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA) was described in 2016 and had its case series published. This study aimed to present the largest TOETVA case series performed in Turkey.Material and Methods: Data from 52 patients who underwent TOETVA procedure between February 2018 and October 2019 were analyzed retrospectively. Demographic data, duration of operation, blood loss, rate of conversion to open surgery, radiological findings, pathological outcomes, and complications we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
4
Order By: Relevance
“…Moreover, unlike other remote-access surgeries that require extensive flap dissection, TOETVA only requires minimal dissection (similar to conventional open thyroidectomy) and provides an exceptional magnified view of the surgical field (17). Many studies have also reported the promising safety and outcomes of TOETVA, by showing comparable complication rates to that of traditional open thyroidectomies (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unlike other remote-access surgeries that require extensive flap dissection, TOETVA only requires minimal dissection (similar to conventional open thyroidectomy) and provides an exceptional magnified view of the surgical field (17). Many studies have also reported the promising safety and outcomes of TOETVA, by showing comparable complication rates to that of traditional open thyroidectomies (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Para la colocacio ´n de tro ´cares se empleo ´una mediana de 14 min (12-15), con una duracio ´n mediana de 80 min (65-100) las lobectomı ´as y 140 min (125-173) la tiroidectomı ´a total. La mediana de tiempo empleado en el VGCCI fue de 30 min (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Para la extraccio ´n de la pieza se emplearon 10 min (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Resultsunclassified
“…De todos los anteriores, solo la TOETVA evita la cicatriz visible, al realizarse por un orificio natural. La casuı ´stica de la cirugı ´a transoral en la literatura es muy variable (desde 5 a 260 casos) 13,[19][20][21][22][23][24][25][26][27] debido, probablemente, a la dificultad de encontrar pacientes adecuados por los estrictos criterios de inclusio ´n y por la baja demanda de este abordaje en Occidente, al no considerarse un estigma las cicatrices cervicales.…”
Section: Discusio ´Nunclassified
“…Furthermore, the use of carbon dioxide (CO2) for insufflation has led to the introduction of new scope of complications. Subcutaneous surgical emphysema, hypercarbia and CO2 embolism has been reported in the literature [ 8 , 22 ]. The first two complications are due to high intra-cavity pressure.…”
Section: Discussionmentioning
confidence: 99%
“…At a later date, the natural orifice transluminal endoscopic surgery (NOTES) was introduced in thyroid surgery in 2008 [ [5] , [6] , [7] ]. Initially the access was via a sublingual or trans-tracheal approach [ 8 ]. These techniques resulted in severe tissue damage and were associated with high complication rates [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%